Factors Influencing the Use of Online Registration Applications in Hospitals: A Systematic Review - Istriyah Istriyah; Fery Agusman Motuho Mendrofa; Blacius Dedi (GLOBAL HEALTH SCIENCE GROUP, 2026)
Advances in information and communication technology have driven digital transformation in the healthcare sector, including patient registration systems in hospitals. Online registration applications have been developed to increase efficiency, reduce queues, and accelerate access to services. However, adoption remains low and is influenced by various individual, technical, and structural factors. This study aims to identify factors that influence the use of online registration applications in hospitals, so that it can provide a comprehensive picture for the development of digital-based services. The study used a systematic review method with PRISMA guidelines. Literature sources were searched through Google Scholar, Semantic Scholar, ProQuest, and ScienceDirect with related keywords. Inclusion articles were published between 2015 and 2025, were quantitative, descriptive, survey, or cross-sectional, and discussed factors influencing the use of online registration applications in hospitals. The keywords used were application, online registration, determinant factors, and hospital. Of the 1,060 articles screened, 9 articles were selected for analysis. A total of 9 articles were synthesized based on the findings of what factors influence the use of online registration applications in hospitals. The review identified five key factors influencing the use of online registration applications: perceived usefulness, perceived ease of use, patient satisfaction, social influence and trust , and facilitating conditions and regulations. These factors operate simultaneously in shaping patient intentions and behavior toward online registration applications. Online registration applications in hospitals are more accepted when they are perceived as useful, easy to use, increase patient satisfaction, and are supported by social factors, trust, and adequate regulations. These findings can inform hospital strategies and health policies to increase the use of digital applications.